A Burkean analysis of the Common Core State Standards: revealing motive by analyzing the agent-purpose ratio and critiquing the standards with a postcolonial lens - Lemming, Megan C., author; Kiefer, Kathleen, advisor; Coke, Pamela, committee member; Aragon, Antonette, committee member (Colorado State University. Libraries, 2014)
Public schooling in the United States undergoes frequent, large-scale reforms based on current political, social, and economic conditions. Such conditions influence the demand for students to master particular literacies and discourses. The Common Core State Standards, a recent educational reform measure that has been adopted by forty-six states, indicate what students need to know and be able to do at the end of each grade level in certain content areas. Examining particular aspects of the Common Core State Standards, such as the agents involved and their purpose in creating and implementing the Standards, helps to reveal implicit motives driving the implementation of the Common Core State Standards. This thesis seeks to reveal such motives in order to illuminate which literacies, literacy practices, and discourses are privileged in public schooling today. My findings indicate that the Common Core reinforces a Western, hegemonic, patriarchal discourse, which has the potential to Other non-dominant discourses and alienate students belonging to marginalized populations. Space exists, however, for teachers to employ pedagogies and methods that challenge this discourse, which ultimately can increase student agency and promote the democratic ideals of public education.
Keywords: arts; analysis; core; language; rhetorical; common